1998
DOI: 10.1177/000841749806500505
|View full text |Cite
|
Sign up to set email alerts
|

Voluntarism as Occupation

Abstract: An exploratory, single-case design was conducted to explore and describe the personal experience of a voluntarism occupation for one individual with schizophrenia who resides within the community. Non-participant observation and in-depth interviewing were utilized to explore the voluntarism experience of this individual. The findings suggest that voluntarism is both a meaningful and purposeful occupation for this individual. Volunteering is perceived to be a valued and socially acceptable occupation which allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 16 publications
(31 reference statements)
4
37
0
1
Order By: Relevance
“…To seek others with similar experiences is a way to normalize one's situation by sharing it with others in the same situation (28,31). The activities performed outside the home environment could be the accepting social context within which persons with schizophrenia may feel competent and valued (33), leading to facilitating social interaction in activity performance. In Sweden it is necessary to be assessed by a public authority in order to receive support for everyday activities performed at home.…”
Section: Discussionmentioning
confidence: 99%
“…To seek others with similar experiences is a way to normalize one's situation by sharing it with others in the same situation (28,31). The activities performed outside the home environment could be the accepting social context within which persons with schizophrenia may feel competent and valued (33), leading to facilitating social interaction in activity performance. In Sweden it is necessary to be assessed by a public authority in order to receive support for everyday activities performed at home.…”
Section: Discussionmentioning
confidence: 99%
“…Social support has a well-documented positive effect on the recipient as well as the provider of support (Bower & Greene, 1995;Rebeiro & Allen, 1998;Reid & Reid, 2000). Furthermore, recent studies have demonstrated that social support is not always positive (Reifman, Biernat, & Lang, 1991;Thomas, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Pascall and Hendey (2004) regarded work as an invaluable activity to assist young people with disabilities to move from a dependent to independent status. Additionally, studies by Kennedy-Jones et al (2005), Legault and Rebeiro (2001), Allen (1998), andStrong (1998) found that engaging in productive occupations positively transformed the identities of people who have experienced mental illness. In this study, engaging in productive occupation helped the participants develop an identity as a productive member of society that in turn boosted the participants' self-esteem because they believed that they were doing something worthwhile.…”
Section: Responsibility and Identitymentioning
confidence: 99%
“…Employment was found to provide powerful protective factors against mental ill-health, such as valuable relationships, a sense of identity, and structure within participants' lives (Strong). Rebeiro and Allen (1998) used an exploratory single-case design, which revealed that voluntary work for one individual with schizophrenia contributed to his mental well-being. Similarly, voluntary work afforded the opportunity for the participant to contribute and be a productive member of society, which helped him construct a socially acceptable identity (Rebeiro & Allen).…”
Section: Introductionmentioning
confidence: 99%